Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Bank Maybank Indonesia Kantor Cabang Sutomo Kota Jambi - M Haris (Science of Management and Students Research Journal (SMS), 2019)
With the increasing number of employees each year results in a lack of work space and a salary increase of less than 2% can affect employee performance and also still a small number of recruited marketing employees have an impact on the achievement of branch offices. The research aims to learn how the influence of the work environment and motivation and performance job of Bank Maybank Indonesia Of Sutomo Of Jambi City. The method used is descriptive quantitative methods. The analysis tool used is multiple linier regression analysis, coefficient correlation and determination, F and T test. And the object  of this research is Bank Maybank of Indonesia Branch Office Sutomo of Jambi City. Results SPSS 20 get regeression equation Y = 9.500 – 0.064 X1 + 0.259 X2. Correlation between work environment and motivation performance against employee activity in Bank Maybank of Indonesia Branch Office Sutomo of Jambi City. Determination test, the earned value of adjusted r2 is 0.155 this amount states that the variable X1 or X2  is able to explain the variabel Y of employee performance in Bank Maybank of Indonesia Branch Office Sutomo of Jambi City amounts 15.5% and the rest 84.5% if be caused by other variables outside variables studied. The Work Environemt and Motivation Employee based hypothesis testing is known that there is a significant relationship between work environment and motivation performance against employee activity in Bank Maybank of Indonesia Branch Office Sutomo of Jambi City, Employees continue to have work to keep and maintain or improve performance. Leader should give rewards to employees who successfully demonstrate high performance, then the employee will be motivated to work harder and better in the workplace.